KEDUDUKAN HUKUM HAK ASUH DAN HAK WARIS ANAK YATIM PIATU YANG MASIH DI BAWAH UMUR - Dedi Pahroji; Puti Priyana; Puspita Farahdillah (Universitas Suryakancana, 2022)
An orphan needs special handling because there is a need for a guardian to protect and take care of their interests, including managing the inheritance of their parents. This often causes many problems regarding the distribution of inheritance rights for the child because the child is not yet capable of carrying out legal actions. The writing aims to find out and examine the position of custody of orphans who are underage, the inheritance of orphans who are underage and the judge's consideration of the custody of orphans who are underage based on the case decision Number 3315/Pdt.G/2021 /PA.JB. The research method used in this paper uses normative juridical which is carried out by examining secondary data consisting of primary, secondary and tertiary legal materials. The data collection technique is done by means of literature study. Based on the research and the results obtained are that the custody of a child who is underage under Islamic law falls to the mother or the mother's family. The inheritance part of an orphan who has a kinship relationship with his parents is included in the ashabah group which is obtained after the inheritance is calculated from the remaining inheritance of the other heirs. The decision of the case Number 3315/Pdt.G/2021/PA.JB that the judge granted the entire claim of the plaintiffs.Keywords: Orphans, Custody, Inheritance Rights.